The Effects of Visual Search and Marketing Through TikTok on Consumer Interaction and Purchasing Decisions for Local Fashion Products in Jakarta - Retno Wulansari; Dila Padila Nurhasanah; Paramita Andiani (Westscience Press, 2025)
This study examines The Impact of Visual Search and Marketing Through TikTok on Consumer Interaction and Purchasing Decisions for Local Fashion Products in Jakarta. The rapid rise of short-form video platforms and image-based search tools has transformed how consumers discover and purchase fashion products. Using a quantitative research design, data were collected from 180 respondents who actively engage with TikTok and visual search features when shopping for local fashion items. The data were analyzed using Structural Equation Modeling (SEM) with PLS 3.0 software. Results show that both visual search and TikTok marketing have significant positive effects on consumer interaction and purchasing decisions. Among the two, TikTok marketing exhibits the strongest influence, confirming the platform’s effectiveness in fostering engagement and driving purchase intention. Furthermore, consumer interaction acts as a mediating variable, strengthening the relationship between marketing stimuli and purchase behavior. The findings highlight that integrating visual search optimization and interactive TikTok marketing strategies can enhance brand visibility, consumer engagement, and sales performance for local fashion businesses in Jakarta.